Ocena psychicznej zdolności do zawarcia małżeństwa u osób z zaburzeniami psychicznymi - Kocur, Józef; Pobocha, Jerzy (Ius Matrimoniale, 2011)
In the present paper the author presented the causes, mechanisms and results of the mental criteria of assessing capacity to contract a marriage according to the regulations of Family and Guardianship Code and Canonical Law. The author conducted comparative analysis of these records in the aspect of forensic-psychiatric assessment. Special attention was paid to the necessity of individualization of opinions in relation to the duration of the disorders, their type, intensity and their impact on specific cognitive, emotional and motivational functions. Evaluating the impact of the disorders on these dispositions should be of greatest importance in such assessment as they help to comprehend significant marital rights and duties and enable the performance of these duties.